Evaluasi Desain Struktural Hoist Crane 16 Ton di PLTM Pantan Cuaca 4,5 MW di Provinsi NAD - Hasibuan, M. Husni Malik; Ariansyah, Muhammad Diaz; Pasaribu, Bangun (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
Power House (PH) is one of the buildings that functions as a production house that produces electrical energy. In general, the power house structure at mini hydro power plants (PLTM) in Indonesia uses heavy steel structures. The design criteria and technical planning of steel structures in the power house used include SNI 1726; 2019, SNI 1727; 2020, SNI 1729; 2020, SNI 7860; 2020, and SNI 7972;2020. The calculation of steel structures in power houses uses the LRFD (Load And Resistance Factor Design) method and for structural analysis ETABS software is used. Analysis of the power house structure is carried out to check the condition of the existing design of the profile used while re-analysis is carried out to obtain a safe profile for use in the power house. Based on the results of the analysis obtained that the WF 400x200x8x13 profile steel is still safe to use as the main column in the power house structure. For beams, the profile steel that is safe to use is WF 300x150x6.5x9. As for the runway beam and column bracket (console beam) still use the existing steel profile design, namely WF 500x200x10x16